Diagnosis and treatment of mucocele in a pediatric patient: case report - Luana Santos MAGALHÃES; Mirian Noé do Bomfim CALAZANS; Ana Lídia Soares COTA; Mariana Alencar NEMEZIO; Marcus Antônio BRÊDA JUNIOR (RGO: Revista Gaúcha de Odontologia, 2020)
ABSTRACT Mucocele is a benign lesion, originating from disorders of minor salivary glands containing mucus. These lesions are found in children and young adults and usually occur due to local trauma. Clinically, it presents as a circumscribed, asymptomatic, soft and bluish or normocromic blister. The treatment of choice is surgical removal, when the lesion does not rupture naturally. This study aims to report a clinical case of mucocele in a pediatric patient removed through total surgical excision. A 7-year-old patient accompanied by mother sought care at the Dentistry Clinic of the “Tiradentes” University Center (UNIT / AL), with a main complaint of asymptomatic blister in the lower lip for about 15 days. In the anamnesis, the habit of biting in the region was reported. At clinical examination, a blister with clear limits of approximately 10 mm in diameter was observed in the lower lip mucosa, with slightly firm/fibrous consistency, which gave rise to doubts about the possible diagnosis, since it presented characteristics similar to that of a mucocele, although consistency at palpation indicates possible fibroma. Surgical excision of the lesion was performed; the material collected was fixed in 10% formalin and sent to histopathological examination that confirmed the diagnosis of mucocele. The patient was kept on follow-up, and there was no recurrence of the lesion. Surgical excision demonstrated an effective and prognostic therapeutic course, allowing accurate diagnosis through the histopathological evaluation of the lesion.